Brain mitochondrial dysfunction and driving simulator performance in untreated obstructive sleep apnea. (15th September 2021) - Vakulin, Andrew; Green, Michael A.; D'Rozario, Angela L.; Stevens, David; Openshaw, Hannah; Bartlett, Delwyn; Wong, Keith; McEvoy, R. Doug; Grunstein, Ronald R.; Rae, Caroline D.
Abstract: It is challenging to determine which patients with obstructive sleep apnea (OSA) have impaired driving ability. Vulnerability to this neurobehavioral impairment may be explained by lower brain metabolites levels involved in mitochondrial metabolism. This study compared markers of brain energy metabolism in OSA patients identified as vulnerable vs resistant to driving impairment following extended wakefulness. 44 patients with moderate‐severe OSA underwent 28hr extended wakefulness with three 90min driving simulation assessments. Using a two‐step cluster analysis, objective driving data (steering deviation and crashes) from the 2nd driving assessment (22.5 h awake) was used to categorise patients into vulnerable (poor driving, n  = 21) or resistant groups (good driving, n  = 23). 1 H magnetic resonance spectra were acquired at baseline using two scan sequences (short echo PRESS and longer echo‐time asymmetric PRESS), focusing on key metabolites, creatine, glutamate, N ‐acetylaspartate (NAA) in the hippocampus, anterior cingulate cortex and left orbito‐frontal cortex. Based on cluster analysis, the vulnerable group had impaired driving performance compared with the resistant group and had lower levels of creatine (PRESS p  = ns, APRESS p  = 0.039), glutamate, (PRESS p  < 0.01, APRESS p  < 0.01), NAA (PRESS p  = 0.038, APRESS p  = 0.035) exclusively in the left orbito‐frontal cortex. Adjusted analysis, higher glutamate was associated with a 21% (PRESS) and 36% (APRESS) reduced risk of vulnerable classification. Brain mitochondrial bioenergetics in the frontal brain regions are impaired in OSA patients who are vulnerable to driving impairment following sleep loss. These findings provide a potential way to identify at risk OSA phenotype when assessing fitness to drive, but this requires confirmation in larger future studies.